The effectiveness of the PIUSE platform in research management and its relationship with the intensive use of the internet by thesis committee members and advisors - Miranda, Percy Samuel Yabar; Vallejo, Natali Kennet Paca; Mendizabal, Brenda Karen Salas; Betancur, Heber Nehemias Chui (O Mundo da Saúde, 2024)
The study aimed to evaluate the effectiveness of the PIUSE platform in managing research processes and the excessive use of the internet by advisors and thesis committee members in the second specialization program at the Faculty of Education of the National University of Altiplano in Puno. This research had a quasi-experimental design, conducted with 125 professors who participated as committee members and/or advisors, with an average age of 46.86±7.87 years. Three instruments were used in the study: a questionnaire for the review of research projects and reports (α=0.967); a questionnaire for the approval of research projects and reports (α=0.894); and a questionnaire for the defense of research projects and reports (α=0.882). The Wilcoxon test was used to compare two related samples before and after the implementation of the PIUSE platform, and Pearson's chi-square test was used to examine the association between internet use and the level of participation. Analyses were performed using IBM SPSS v.25. The PIUSE platform, built with Google tools, significantly influenced the efficiency in the review and approval of research projects and reports (Z=-9.729; p<0.001), the review of information exchange (Z=-9.702; p<0.001), and the editing and correction during the review of research projects and reports (Z=-9.766; p<0.001). However, 85.4% of the professors who participated as committee members at a high level used the internet for more than 4 hours/day (α2=43.427; P<0.001).